Public Health Shock, Intervention Policies, and Health Behaviors: Evidence from COVID-19 - Hasanzadeh, Samira; Alishahi, Modjgan (Review of Economic Analysis, 2022)
In response to the COVID-19 pandemic, many countries, including the U.S., adopted intervention policies aimed at averting the spread. However, these policies may have led to significant changes in public health behaviors. We use Google search queries to examine how state government actions are associated with people’s internet searches (internet browsing habits) related to health behaviors. We employ the di erences-in-di erences method to determine the link between disease outbreak, associated intervention policies, and changes in health behavior related searches. Our findings show that school closures, restaurant restrictions, and stay-at-home orders lead to a significant rise in searches for workout, physical activity, exercise, takeout, liquor, and wine. Moreover, people’s concerns regarding weight loss, diet, nutrition, restaurant, and fast food substantially decline following stay-at-home orders. Our event-study results indicate that changes in health behaviors began weeks before stay-at-home orders were implemented contemporaneously with emergency declarations and other partial closures. These findings suggest that people’s health behaviors are notably a ected by state government’s intervention policies.